The Mediating Role of Cultural Intelligence in the Relationship between the Openness to Experience Personality Trait and Job Satisfaction among Expatriates - Lie, Daniel; Suyasa, P. Tommy Y. S.; Wijaya, Erik (UI Scholars Hub, 2021)
This study has explored the role of cultural intelligence as a mediator in the relationship between the openness to experience personality trait and job satisfaction among expatriates. Expatriates were required to fill up online questionnaires to measure all the three variables. This study used a regression and bootstrapping analysis to test the hypothesis in a sample of 265 expatriates. The result indicates that the variance in job satisfaction accountable to the openness to experience personality trait is fully mediated through cultural intelligence. This finding provides evidence that possessing cultural intelligence acts as a mechanism in which an open expatriate could feel satisfied with his or her job. Moreover, this study discusses the practical implications especially for multinational companies and suggests some future research directions.